CHILDREN'S AGE WHEN GETTING COMPLEMENTARY FOOD AND SHORT STATURE EVENTS IN CHILDREN 12-24 MONTHS - Kristianingrum, Adisti; Pangemanan, Lisa; Christine, Ika (JOURNAL OF WIDYA MEDIKA JUNIOR, 2021)
Introduction: Short stature remains a nutritional problem in Indonesia. World HealthOrganization (WHO) data showed that Indonesia is the third-highest ranked for short stature prevalence among countries in Southeast Asia. National Basic Health Research (Riskesdas) in 2013 stated that the prevalence of short stature children was 37.2%. Short stature is caused by various factors, and one of the causes is early complementary feeding. Purpose: To analyze the association between child age when receiving complementaryfeeding and short stature in children 12-24 months. Method: This research was an observational analytic study with a cross-sectional design.Sampling technique using non-probability sampling, i.e., consecutive sampling. Datacollected through interviews, questionnaires, and physical examinations of children's bodylength and weight. Research location was in the working area of the Sidorejo Community Health Center. Statistical analysis using Chi-square test. There were 182 subjects included in this study. Results: Among those who received complementary feeding before six monthsold, 53 children (76.8%) had short stature, and 16 children (23.2%) were normal. Meanwhile, after six months old, those who received complementary feeding were 40 children (35.4%) who had short stature, and 73 babies (64.4%) received complementary foods after six months with normal growth. Chi-square test showed a significant association between child age when receiving complementary feeding and short stature among children aged 12-24 months in the working area of the Sidorejo Community Health Center (p<0,001; PR = 2.17, 95% CI=1.642.87).Conclusion: There is a significant relationship between child age when receivingcomplementary feeding and short stature in the working area of the Sidorejo Community Health Center.